218 Reframing the JTF Clinical Trial Competencies from a CRP Team Science Perspective. (April 2022) - Kolb, Robert H.; Jones, Carolynn; Fritter, Jessica; Carter, Karen; Summerside, Nicole; Exe, Nicole; Sprecher, Jennifer; Kopras, Elizabeth; Saldana, Ty; Aslaner, David; Hildreth, Laura; Thanthaeng, Nopporn; et al.
Abstract : OBJECTIVES/GOALS: Our goal is to explore and collaboratively identify the team science competencies essential for Clinical Research Professionals at all experience levels and how these competencies relate to the Joint Task Force for Clinical Translational Research Professionals Competencies. METHODS/STUDY POPULATION: Team science competencies for clinical research professionals are poorly defined. The JTF Clinical Trial Competencies lack sufficient emphasis on team science, though it is briefly included in two JTF competency domains: Leadership & Professionalism, and Communication & Teamwork. The competencies primarily focus on tasks related to clinical research and basic knowledge of product development; however, a conceptual model for applying the competencies using a team science lens is needed. Currently, the JTF competency figure is often thought of as sequential, given the competencies are numbered, creating the misconception that the last competencies are less important. We support a new figure showing the permeability of team science across competencies and the connectedness and equality of the competencies. RESULTS/ANTICIPATED RESULTS: Our anticipated results are to show the integral nature of team science in clinical research professional communities of practice. Once complete, we will have identified measurable team science competency-based skills essential for clinical research professionals at various levels of expertise. Understanding the multi-dimensional team science competencies will inform targeted team science education and training for clinical research professionals. Our revised competency framework provides an improved team science conceptual model for clinical translational science. DISCUSSION/SIGNIFICANCE: Our work will define team science competencies as related to clinical research professionals at all experience levels. The interdependence of teams across clinical trial activities necessitates a consideration of an improved conceptual framework for clinical translational team science competencies.